The Battle for Pakistan : The Bitter US Friendship and a Tough Neighbourhood - Shuja Nawaz (Karachi Liberty Publishers, 2020)
Based on detailed interviews with key US and South Asian leaders, access to secret documents and operations, and the author's personal relationships and deep knowledge of the region, this book untangles the complex web of the US-Pakistani relationship and identifies a clear path forward, showing how the United States can build better partnerships in troubled corners of the world.
Include Bibliography and Index
Keywords: Pakistan Movement -- Internal Battles -- Mil-to-Mil Relations -- Pakistan -- Diplomatic relations -- United States -- Foreign relations -- Pakistan